Mengenal Literasi Keuangan Rumah Tangga di Desa Metenggeng Purbalingga - Widyahayu Warmmeswara Kusumastati; Yusriyati Nur Farida; Agus Faturokhman; Sugiarto Sugiarto (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
Household financial literacy plays a crucial role in supporting family welfare and economic resilience in rural communities. Limited understanding of financial management often leads to imbalances between income and expenditure, low saving capacity, and inadequate long-term financial planning. This community service activity was conducted in Metenggeng Village, Purbalingga Regency, aiming to enhance household financial literacy through education and simple mentoring. The implementation method included problem identification, financial literacy education, interactive discussions, and assistance in preparing household budgets. The results indicate an improvement in participants’ understanding of income management, expenditure control, and the importance of family financial planning. This activity is expected to encourage more prudent and sustainable financial behavior among rural households